Methods of teaching primary school pupils reading in English - І. В. Шастова (Іноземні мови, 2013)
The article provides a brief review of methods in teaching reading skills in order to find the optimal way for a particular age group. The analysis includes some works of scientists and researchers who are involved in this problem. A number of techniques that can be used when teaching English reading skills has been ascertained. The earlier typology of existing methods has been determined.